Enhancing the intrinsic p-type conductivity of the ultra-wide bandgap Ga2O3 semiconductor. Issue 33 (6th August 2019) - Chikoidze, Ekaterine; Sartel, Corinne; Mohamed, Hagar; Madaci, Ismail; Tchelidze, Tamar; Modreanu, Mircea; Vales-Castro, Pablo; Rubio, Carles; Arnold, Christophe; Sallet, Vincent; Dumont, Yves; Perez-Tomas, Amador
Abstract : Strongly compensated Ga2 O3 is shown to be an intrinsic (or native) p-type conductor with the largest bandgap for any reported p-type transparent semiconductor oxide which may shift the frontiers in fields such as power electronics and photonics. Abstract : While there are several n-type transparent semiconductor oxides (TSO) for optoelectronic applications ( e.g. LEDs, solar cells or display TFTs), their required p-type counterpart oxides are known to be more challenging. At this time, the n-type TSO with the largest bandgap (∼5 eV) is Ga2 O3 that holds the promise of extending the light transparency further into the deep ultraviolet. In this work, it is demonstrated that strongly compensated Ga2 O3 is also an intrinsic (or native) p-type TSO with the largest bandgap for any reported p-type TSO ( e.g. NiO, SnO, delafossites, oxychalcogenides). The achievement of hole mobility in excess of 10 cm 2 V −1 s −1 and (high temperature) free hole concentrations in the ∼10 17 cm −3 range challenges the current thinking about achieving p-type conductivity in Ga2 O3 being "out of the question". The results presented in this paper therefore further clarify that p-type Ga2 O3 is possible, although more research must be conducted to determine what are the real prospects for Ga2 O3 solar blind bipolar optoelectronics and ultra-high power electronics based on p–n homojunctions.